2020
DOI: 10.3390/en13123198
|View full text |Cite
|
Sign up to set email alerts
|

Design and Thermo-Economic Comparisons of an Absorption Air Conditioning System Based on Parabolic Trough and Evacuated Tube Solar Collectors

Abstract: Solar absorption cycles for air conditioning systems have recently attracted much attention. They have some important advantages that aid in reducing greenhouse gas emissions. In this work, design and thermo-economic analyses are presented in order to compare between two different collector types (parabolic trough and evacuated tube) by water–lithium bromide absorption systems, and to select the best operating conditions. Generally, the system consists of three major parts. The first part is the solar field fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…An essential aspect in the dimensioning and manufacturing of the NH 3 /LiNO 3 working fluids for absorption refrigeration systems is the no need for rectification components and with the possibility of using solar energy as the exclusive activation source as shown [19,20,121,125]. Many factors have been considered in the selection and use of these chemical components in the working fluids, as well as the use of compact heat exchangers that use loads of relatively small mixtures, leading to the construction of smaller absorption chillers [26,27,62,126], but with capacities similar to the commercial ones [127,128].…”
Section: Final Considerations On the Absorption Refrigeration Systems...mentioning
confidence: 99%
“…An essential aspect in the dimensioning and manufacturing of the NH 3 /LiNO 3 working fluids for absorption refrigeration systems is the no need for rectification components and with the possibility of using solar energy as the exclusive activation source as shown [19,20,121,125]. Many factors have been considered in the selection and use of these chemical components in the working fluids, as well as the use of compact heat exchangers that use loads of relatively small mixtures, leading to the construction of smaller absorption chillers [26,27,62,126], but with capacities similar to the commercial ones [127,128].…”
Section: Final Considerations On the Absorption Refrigeration Systems...mentioning
confidence: 99%
“…The main objective of this research was to design, construct, and test the solar ethanol distillation system. The researcher had foreseen these problems from the findings of previous research, which provided guidelines for modifying and developing the design of the solar ethanol distiller so as to increase the efficiency of the ethanol distillation [29]. The modified design uses the heat absorber core in an evacuated tube solar collector type to reduce the heat loss of the heat absorber core and also uses electronic devices for controlling the distillation temperature of the solution concentration to be maintained within an appropriate range.…”
Section: Introductionmentioning
confidence: 99%
“…In this period, several configurations have been studied and analyzed in terms of stages, absorberrefrigerant pairs, drive medium, applications and cooling capacities. In the literature, studies of solar cooling thermal systems have been found with single-effect absorption machines and driven by various types of solar collectors: with nonconcentrating or stationary solar collectors [4,5,6,7,8,9,10,11,12,13,14,15,16], with parabolic cylinder collectors [6,14,17,18] and with linear Fresnel collectors [19]. Also, systems with absorption machines with two or more stages and with various types of solar collectors: with parabolic cylinder collectors [4,20] and with linear Fresnel collectors [21].…”
Section: Introductionmentioning
confidence: 99%
“…Esta herramienta se basa en un modelo matemático integrado que considera las condiciones ambientales, las cargas térmicas del edificio, los datos de pre-dimensionamiento de cada componente del sistema y la interacción simultánea entre ellos, para realizar un análisis preciso, simple y realista. Del caso de estudio, realizado en el mes de julio con 704 m 2 de apertura solar y un tanque de almacenamiento de 35200 L, se obtuvieron 47,5 MWh de energía de refrigeración, con una reducida contribución del sistema auxiliar (5,6 MWh) y una mínima cantidad de horas de desactivación del sistema de captación solar (0,7 %). El coeficiente de rendimiento (COP) diario de la máquina de absorción se mantuvo sobre 0,69.…”
unclassified